2021
DOI: 10.1155/2021/5540895
|View full text |Cite
|
Sign up to set email alerts
|

A Lightweight Intelligent Intrusion Detection Model for Wireless Sensor Networks

Abstract: The wide application of wireless sensor networks (WSN) brings challenges to the maintenance of their security, integrity, and confidentiality. As an important active defense technology, intrusion detection plays an effective defense line for WSN. In view of the uniqueness of WSN, it is necessary to balance the tradeoff between reliable data transmission and limited sensor energy, as well as the conflict between the detection effect and the lack of network resources. This paper proposes a lightweight Intelligen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Hence, the IDS is one of the most suitable option for WSN security, which supports to spot the intrusions or unauthenticated activities in the network by analyzing the features of network and data. Pan, et al [24] deployed a lightweight and intelligent intrusion detection model for guaranteeing the privacy, security, and con dentiality of WSN. Here, the K-Nearest Neighbor (KNN) algorithm incorporated with the Sine Cosine Algorithm (SCA) was utilized to minimize the false alarm rate and increase the classi cation accuracy of this detection framework.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, the IDS is one of the most suitable option for WSN security, which supports to spot the intrusions or unauthenticated activities in the network by analyzing the features of network and data. Pan, et al [24] deployed a lightweight and intelligent intrusion detection model for guaranteeing the privacy, security, and con dentiality of WSN. Here, the K-Nearest Neighbor (KNN) algorithm incorporated with the Sine Cosine Algorithm (SCA) was utilized to minimize the false alarm rate and increase the classi cation accuracy of this detection framework.…”
Section: Related Workmentioning
confidence: 99%
“…Pan et al [28] also proposed a lightweight intelligent IDS model for wireless sensor networks. The authors used KNN and the sine cosine algorithm to design their model.…”
Section: Related Workmentioning
confidence: 99%
“…A parameter is required to measure the lightness of the proposed model. Pan et al [28] also suggested a lightweight intelligent intrusion detection system (IDS) architecture for wireless sensor networks. To create their model, the authors used KNN and the sine cosine technique.…”
Section: Related Workmentioning
confidence: 99%